Obesity and hypertension amongst traders in Ijebu Ode, Nigeria (2015)
Market traders spend most hours of the day sitting down and involved in many other sedentary activities, conditions which increase the risk of chronic diseases. This study was designed to determine the prevalence of obesity and hypertension amongst market men and women in Ijebu- Ode, Nigeria. A cross-sectional study involving 157 (52.3%) males and 143 (47.7%) females was conducted. Body mass index (BMI) was derived from weight and height measurements; waist circumference (WC) measurement was taken to assess abdominal obesity. Blood pressure was measured using a digital sphygmomanometer. The mean(±S.E) age in the study was 39.04(0.658) years, mean(±S.E) BMI, SBP and DBP were 26.36(0.32)kgm-2, 116.64(1.27)mmHg and 79.50(0.86)mmHg respectively. Based on BMI, the prevalence of overweight and obesity were 25.3% and 26.7%. About 52.0% of the respondents had abdominal obesity. Prevalence of both general and abdominal obesity were significantly higher among females than males (p<0.05). The overall prevalence of hypertension was 16.0%. Body Mass Index was significantly related to both systolic and diastolic blood pressure (p<0.05). Obesity and hypertension among market men and women in Ijebu-Ode constitute health issues of public health importance. Sensitization on prevention and control of these disorders is important to protect those in this community from obesity related health challenges.